EVALUASI PROSES BONGKAR MUAT TERHADAP KETEPATAN WAKTU KEBERANGKATAN KAPAL PENUMPANG KM. BUKIT SIGUNTANG - Gabriel Damayanti; Rizal Rochmansyah; Bayu Yudho Baskoro; Riki Wanda; Yusuf Pria Utama (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Cargo handling is a core operational activity in ports that directly affects berth time efficiency and vessel departure punctuality, as any delay in this process will impact the overall sailing schedule. This study aims to analyze the influence of cargo handling operations and passenger boarding on the departure punctuality of the passenger vessel KM Bukit Siguntang and to formulate strategic operational recommendations to improve departure time performance. The study employs a descriptive qualitative approach, with data collected through semi-structured interviews, field observations during Voyage 16.2025, and operational documentation including ETA, ETD, and actual ATD records. Informants consist of ship crews and port operational personnel. Data were analyzed using an interactive analysis model involving data reduction, data display, and conclusion drawing. The findings indicate that the impact of delays is proportional to berth duration; therefore, shorter port stays carry a higher risk of operational time loss. The study recommends the implementation of proportional buffer time, stricter boarding cut-off policies, optimized cargo planning, improved equipment readiness, and the establishment of a monitoring and evaluation system based on key performance indicators to enhance vessel departure punctuality.